Online English Education: A Paradigm Shifts in Education System and Its Challenges - Imam Mujtaba; Yudha Prapantja; Ayesha Khatuni; Muhamad Sofian Hadi (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
The pandemic Covid-19 has made the world face one of the greatest challenges we have ever experienced over a century. Every sector (health industry, education, aviation, navigation, agriculture, media) is confronting such potential catastrophe that all are struggling to survive in this new normal. Due to these unavoidable trying times, there is a paradigm shift, a transition in every sphere. The education fraternity is considered the platform to build up the future generation is suffering the most because of the campus closure where other sectors are allowed to continue their activities so far. It has gone through several transformations from (traditional way of online teaching) to cope up with the situation and still struggling to reach up its goal. There was a chance for loss of the academic year if there was no online education, no transition from the traditional way of the teaching-learning process. This paper is an attempt to focus on the transition of the English teaching-learning process for the continuation of academic performances, the features of online English education, the types of online English education, the role of English teachers in this regard, strategies to make an effective online English class, challenges that we are encountering and some recommendations that are needed for the continuation of English teaching-learning performance during future trying times like epidemic, pandemic, war and so on.